The Influence of Environmental Performance, CEO Character, Media Exposure, and Company Size on Carbon Emission Disclosure in Energy Sector Companies in Indonesia - Navia, Gina; Santoso, Sigit Budi (Lembaga Teewan Journal Solutions, 2026)
This study aims to examine the influence of environmental performance, CEO character, media exposure, and company size on carbon emission disclosure in energy sector companies listed on the Indonesia Stock Exchange for the 2020-2024 period. The background of this study is the increase in greenhouse gas emissions in the Indonesian energy sector, which reached 775.4 million tons of CO₂e in 2023, but was not accompanied by adequate reporting transparency. The study population was all energy sector companies listed on the IDX. A purposive sampling technique resulted in 19 sample companies with a total of 95 observations over five years. Secondary data were obtained from annual reports, sustainability reports, the official IDX website, and the Ministry of Environment and Forestry. The analysis method used panel data regression with the help of SPSS. The results of the simultaneous test showed that all four independent variables together had a significant effect on carbon emission disclosure with an F-value of 17.419 > F-table 2.47 and a significance level of 0.000. Partially, environmental performance has a significant positive effect with a t-count of 3.965 > t-table of 1.986 and a significance of 0.000. Media exposure has a significant positive effect with a t-count of 3.101 > t-table of 1.986 and a significance of 0.003. Company size has a significant positive effect with a t-count of 5.612 > t-table of 1.986 and a significance of 0.000. However, CEO character proxied by tenure does not have a significant effect on carbon emission disclosure with a t-count of 1.727 < t-table of 1.986 and a significance of 0.088. The Adjusted R-Square value of 0.411 means that the four variables are able to explain 41.1 percent of the variation in carbon emission disclosure, while the remaining 58.9 percent is explained by other variables outside the model such as profitability, leverage, and institutional ownership.